The Party Politics of Electoral System Choice - Emmenegger, Patrick; Walter, André (Oxford University Press, 2026)
The Party Politics of Electoral System Choice explores the strategic manipulation of electoral systems by political actors to maintain power. It delves into how electoral systems are more than mere governance tools; they are pivotal instruments that shape power dynamics. The book shows that the choice of an electoral system is one of the most consequential decisions in any democracy. The authors develop a ‘neo-Rokkanian’ theory of electoral system choice, arguing that incumbent parties try to contain electoral threats through district design and electoral alliances. When successful, incumbent parties resist electoral reform. However, this strategy leads to growing seat-vote distortions, which is why disadvantaged parties demand proportional representation. In the absence of any exogenous shock, however, disadvantaged parties will struggle to overcome the incumbent parties’ resistance to electoral reform. If incumbent parties cannot resort to containment measures, for example because the electoral geography is not suitable, they support the adoption of proportional representation. In this response, incumbent parties opt for a more inclusive electoral system that allows them to limit their seat losses in the face of a rapidly growing electoral threat that they cannot neutralize. Through a comprehensive analysis of first-wave democracies and a combination of quantitative and qualitative methods, the authors reveal the broader patterns of strategic behaviour of political actors seeking to optimize their positions through electoral reform. This comprehensive study is essential for understanding the politics of electoral system choice, offering new insights into electoral geography, district design, electoral alliances, and party preferences for electoral reform.